(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
Emphasis on product placement as a variable in the marketing communication strategyof organisations seems to be a relatively new focus. However, evidence exists that asearly as the 1940s product placement was used in feature films to brand products andservices. The initial use of product placements in feature films received new opportunitiesthrough the introduction of new electronic media, such as video, DVD, mobile messaging,electronic billboards, Internet clips and websites. Product placement is not confined tocinema feature films. New electronic media offer unique opportunities for productplacement, which necessitated the renewed focus on product placement as a vehicle ofdeliberate product exposure within the broader integrated marketing communication(IMC) context.The use of product placement has increased rapidly over the last few years. Productnames are increasingly being featured in films and television programmes. Companiesare increasingly seeking to broaden their marketing campaigns to include productplacement in broadcast media to confirm the product’s brand identity or to reach differentaudiences effectively.This article aims to describe the context in which product placement is categorised. Italso explains the relevance of product placement as a vehicle of communication in theintegrated marketing communication strategy.In order to reach the set objectives of this article, a literature review of existing informationwas conducted. The article does not claim to be a comprehensive work on productplacement in general - it rather attempts to provide a theoretical framework in which product placement could be studie